SMART Drug Based Targeted Delivery: A New Paradigm for Nanomedicine Strategies - Sugapriya Dhanasekaran (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2015)
Introduction: Targeted drug delivery systems are nanoscale drug carrier molecules designed for improving the communication of cellular and molecular components and biodistribution of tumour targeted drug (chemo) therapeutics. Nanomaterials are generally clusters of molecules, atoms and molecular fragments into extremely small size particles (1-100 nm) in nature. Nanomaterials engineered as self-assembled biodegradable particles were used for targeted drug delivery system. Nanocarriers/ particles should be- capable of transporting high doses of chemotherapeutic drugs/nanomedicines into the targeted tumor cells without disturbing the normal healthy cells. It is also used for construction of novel  argeted drug delivery system and future application in nanovaccination and nanotechnology. Conclusion: Multifunctional smart nanoparticles or carries hold out the possibility of effective drug targeted therapeutics in molecular and cellular levels at the earliest stage. Here, we briefly discuss the significance of targeting strategies and drug delivery system and outline the current approaches and future directions in the improvement of tumor targeting nanomedicines.